2021
DOI: 10.4103/tdj.tdj_34_20
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary midline diastema among a group of Egyptian adult populations (prevalence and etiology)

Abstract: Purpose This study was performed to identify the prevalence and etiological factors of maxillary midline diastema among a sample of adult patients undergoing orthodontic treatment in orthodontic private clinics in Qaloubya, Fayoum, and Giza governorates. Patients and methods Three hundred seventy-five patients (199 females and 176 males) were included in this study. The full records (intraoral photographies and radiographs) of all patients were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…As for midline diastema, it was noticed that midline diastema was found in 15.7% of participants which was in agreement with Ocaña Caluña and Macías Ceballos, 2021; Rashid and Khalifa, 2021. This finding can be justified by the gradual closure of midline diastema after the clinical eruption of the maxillary permanent canine (Liu, Hsu and Chen, 2013).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As for midline diastema, it was noticed that midline diastema was found in 15.7% of participants which was in agreement with Ocaña Caluña and Macías Ceballos, 2021; Rashid and Khalifa, 2021. This finding can be justified by the gradual closure of midline diastema after the clinical eruption of the maxillary permanent canine (Liu, Hsu and Chen, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…On the contrary, Luqman et al, 2011; Rashid and Khalifa, 2021 reported highly attached frenum as the second most prevalent cause of midline diastema which might be justified by the lateral incisors and canines eruption that hinders spontaneous closure of diastema as a normal pathway of occlusion development, this make it difficult for the highly attached frenum to change its position and migrate nasally with age (Rashid and Khalifa, 2021).…”
Section: Discussionmentioning
confidence: 99%